2005
DOI: 10.1108/09649420510635213
|View full text |Cite
|
Sign up to set email alerts
|

Constraints facing working women in Lebanon: an insider view

Abstract: Purpose -The ascendancy of women to top management positions is a perennial problem plaguing organizations worldwide. The purpose of this paper is to present some insights relating to this pervasive phenomenon from a Middle Eastern context by exploring the constraints reported by Lebanese women managers throughout their careers. Design/methodology/approach -Literature review and qualitative research methodology consisting of interviews with 62 Lebanese women managers in different fields of occupation. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
151
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(164 citation statements)
references
References 22 publications
13
151
0
Order By: Relevance
“…According to Jamali, Sidani and Safieddine (2005), Lebanon is an Arab country and a setting up associate from the Arab partnership. Additionally, it is a pluralistic nation by splendor.…”
Section: Methodsmentioning
confidence: 99%
“…According to Jamali, Sidani and Safieddine (2005), Lebanon is an Arab country and a setting up associate from the Arab partnership. Additionally, it is a pluralistic nation by splendor.…”
Section: Methodsmentioning
confidence: 99%
“…Two of these studies are (Jamali, Sidani, & Safieddine, 2005), (Kattara, 2005), (Al-Lamky, 2007), and (Tlaiss & Kauser, 2010). While Jamali, et al, (2005) and Tlaiss and Kauser (2010) focused on constraints as perceived by Lebanese women managers in some occupation fields.…”
Section: Related Studiesmentioning
confidence: 99%
“…Kattara (2005) focused on career challenges encountered by female managers in hotels in Egypt, whereas Al-Lamky (2007) examined challenges encountered by Arab women managers in Oman. Jamali et al (2005) intended to assess constraints faced by Lebanese women mangers. Employing interview, they collected data from 52 Lebanese female mangers and found that constraints facing Lebanese female managers can be classified into three main categories: socio-cultural aspects (cultural variables), corporate environment (stereotypical attitudes towards women and family and domestic commitments) and the structural constraints (exclusion from formal and informal network, absence of relevant benefits, and developmental assignments designed exclusively for male managers).…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations